VD_FINDINFO Jug / 2023 / 246 vom 21. November 2022 - VD Tribunal cantonal (2022)
BLANCHIMENT D'ARGENT, LOI FÉDÉRALE SUR LES STUPÉFIANTS ET LES SUBSTANCES PSYCHOTROPES, CONCOURS D'INFRACTIONS, EXPULSIONDROIT PÉNAL, REJET DE LA DEMANDE | 305bis ch. 1 CP, 49 al. 1 CP, 66a al. 1 let. o CP, 19 ch. 1 al. 2 LStup, 19 ch. 1 al. 3 LStup, 19 ch. 1 al. 4 LStup, 19 ch. 1 al. 7 LStup, 19 ch. 2 let. a LStup, 19 ch. 2 let. b LStup, 115 al. 1 let. b LEI